2018
DOI: 10.1039/c8ra06626d
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of anisotropic wetting of chemically striped surfaces

Abstract: In this paper, the measurement process of advancing and receding contact angles (CA) in experiments is simulated using Surface Evolver (SE). The normalized energy of the droplet is calculated by fixing the three-phase contact line that lies at the boundary between stripes and by changing the droplet volume.The most stable wetting state is determined for each stripe configuration. The slip-jump behavior of the three-phase contact line is observed. Furthermore, a small wet stripe width and large dry stripe width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The free energy of the system G is expressed as where A lv is the contact area of the liquid, γ lv is the liquid–vapor interfacial tension, and θ is the contact angle. This free energy G is normalized by γ lv to achieve the equilibrium droplet shape . The contact angle is defined by Young’s equation , where γ lv is the liquid–vapor interfacial tension, γ sv is the solid–vapor interfacial tension, and γ sl is the solid–liquid interfacial tension.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The free energy of the system G is expressed as where A lv is the contact area of the liquid, γ lv is the liquid–vapor interfacial tension, and θ is the contact angle. This free energy G is normalized by γ lv to achieve the equilibrium droplet shape . The contact angle is defined by Young’s equation , where γ lv is the liquid–vapor interfacial tension, γ sv is the solid–vapor interfacial tension, and γ sl is the solid–liquid interfacial tension.…”
Section: Methodsmentioning
confidence: 99%
“…This free energy G is normalized by γ lv to achieve the equilibrium droplet shape. 30 The contact angle is defined by Young's equation 31,32 cos ( )…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…It has been found that the increase of surface roughness increases the hydrophobicity of the fibrous structure [22]. The surface energy minimization approach has been successful in the prediction and computation of the shape of droplets on different textures [23][24][25][26][27][28]. Tafreshi et al [29] experimentally and numerically studied the wetting of ferrofluid droplets on fibrous mats.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study the focus lies on chemically patterned striped surfaces which are wetted by water droplets with radii of the order of magnitude of the stripe width. For such kind of systems, static wetting behavior has been studied by using energy minimization techniques [5][6][7], lattice Boltzmann simulations [8,9] and experiments [10]. Also inertia-driven spreading [9] and the splitting [11][12][13] of impinging droplets on such kind of surfaces has been investigated in some detail.…”
Section: Introductionmentioning
confidence: 99%